IMPLEMENTASI METODE LALARAN NAZHOM KITAB TUHFATUL ATHFAL DI PONDOK PESANTREN MASYARIQUL ANWAR PANDEGLANG - Syaefulloh, Syaefulloh (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
The lalaran method is a method of memorizing, repeating memorization and strengthening memorization which is carried out accompanied by musical rhythms so that it is easy to memorize. This study aims to identify the planning, implementation, results and impacts of the implementation of the Lalaran Nazhom Method of the Tuhfatul Athfal Book and the supporting and inhibiting factors of implementation. This study is a descriptive qualitative study, conducted at the Masyariqul Anwar Pandeglang Banten Islamic Boarding School. Data collection was carried out through interviews, observations and documentation. Data analysis used descriptive analysis, validity checks through data triangulation. The results of the study showed: 1) Planning was carried out by analyzing, determining targets, setting implementation times and teaching strategies even though planning was limited to oral and not in written form; 2) Implementation began with congregational prayer, reading the Qur'an to the kyai, reading the matan, explaining the meaning of each sentence, explaining the meaning of the law contained, reading together nazhom accompanied by songs and music (lalaran), closed with hamdalah, greetings and ended with a friendly handshake with the kyai; 3) The results of the lalaran method are that all students memorize the tuhfatul athfal which is displayed in the end of year event so that the students' memorization becomes strong, they are motivated to memorize, they are used to repeating and it helps in understanding and implementing the reading. 4) Supporting factors come from the kyai and students, while inhibiting factors are influenced by the learning atmosphere, boredom, fatigue and personal problems of students.